Leadership and Management Style pada PT PAL Indonesia: Studi Literatur Review - Wahdatul Laili,; Mochammad Isa Anshori, (Journal of Management and Creative Business, 2024)
The success of an organization is determined by the quality of leadership and the leadership style used. Successful leaders are those who are able to manage an organization, influence others constructively, and show the right path and behavior to work together. A management style that supports and motivates employees also has a significant impact on company development. The aim of this research is to analyze and identify the leadership qualities and management styles used in the success of an organization. The method used is a literature review study method, such as from books, journals and several previous studies. The results of this research emphasize the role and influence of leadership and management styles on employee performance, as well as comparisons with relevant previous research. Some of the variables discussed include organizational commitment, motivation, communication and employee performance in the context of leadership, as well as planning, organizing, directing and controlling in the context of management. This research provides a deeper understanding of the importance of integration between leadership and management in achieving organizational goals, as well as various leadership styles and management functions that can influence employee performance and company development.